Clostridium perfringens bacteremia associated with colorectal cancer in an elderly woman - Chia-Yu Huang,; Chia-Yu Huang,; Mu-Cyun Wang,; Mu-Cyun Wang, (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Huang CY, Wang MC. Clostridium perfringens bacteremia associated with colorectal cancer in an elderly woman. Turk J Gastroenterol 2020; 31(12): 960-1.